PENALARAN HUKUM ISLAM TERHADAP DONOR DARAH ANTAR ORANG BERBEDA AGAMA - La Jamaa (TAHKIM, 2020)
Blood transfusion is closely related to the function of human caliphate on the earth at building harmonious relations and benefit for the humanity among fellow, without being limited by differences in belief (religion) between the donor and the recipient. Therefore, blood donor between people of different faiths in the Islamic law perspective is allowed. Similarly the financing at Blood Donor Unit at PMI for the benefit of blood transfusion, is not identical with commercialization (purchase) of blood, so it is allowed in the Islamic law. In addition, blood donors did not lead to the legal consequence in form of the forbidden status of the donor and recipient